Session Hijacking and Prevention Technique - Kumar Baitha, Anuj; Smitha Vinod, Prof. (International Journal of Engineering and Technology, 2018)
Session Hijacking is an attack which is basically used to gain the unauthorized access between an authorized session connections. This is usually done to attack the social network website and banking websites in order to gain the access over the valid session as well as over the website too. These attacks are one of the commonly experienced cyber threats in todayâ€™s network. Most of the websites and networks are vulnerable from this kind of attack.Â For providing the protection I have given the multiple ways to protecting from this session hijacking attack. I have especially focused on one of the major attacks in this session hijacking attack SSL Strip attack which play very vital role in this kind of attack. Sometimes this session hijacking attack is also known as the Man in the Middle attack (MIMA).In this paper, I have covered many security mechanisms to stay away and protect you and the network. This session hijacking attack is very dangers for the security perspective. Even it can steal all usersâ€™ most sensitive data. This can create a big loss for the users financially. From all these types of attack, I have proposed many mechanisms to help the users to stay away from the attack. The main objective of this paper is to give detail information of session hijacking and countermeasure from session hijacking attacks.